Azithromycin enhances the cytotoxicity of DNA‐damaging drugs via lysosomal membrane permeabilization in lung cancer cells - Toriyama, Kazutoshi; Takano, Naoharu; Kokuba, Hiroko; Kazama, Hiromi; Moriya, Shota; Hiramoto, Masaki; Abe, Shinji; Miyazawa, Keisuke (Cancer science, 2021)
Cancer cells use autophagy for growth, survival, and cytoprotection from chemotherapy. Therefore, autophagy inhibitors appear to be good candidates for cancer treatment. Our group previously reported that macrolide antibiotics, especially azithromycin (AZM), have potent autophagy inhibitory effects, and combination treatment with tyrosine kinase inhibitors or proteasome inhibitors enhances their anti–cancer activity. In this study, we evaluated the effect of combination therapy with DNA‐damaging drugs and AZM in non–small‐cell lung cancer (NSCLC) cells. We found that the cytotoxic activities of DNA‐damaging drugs, such as doxorubicin (DOX), etoposide, and carboplatin, were enhanced in the presence of AZM in NSCLC cell lines, whereas AZM alone exhibited almost no cytotoxicity. This enhanced cell death was dependent on wild‐type‐p53 status and autophagosome‐forming ability because TP53 knockout (KO) and ATG5‐KO cells attenuated AZM‐enhanced cytotoxicity. DOX treatment upregulated lysosomal biogenesis by activating TFEB and led to lysosomal membrane damage as assessed by galectin 3 puncta assay and cytoplasmic leakage of lysosomal enzymes. In contrast, AZM treatment blocked autophagy, which resulted in the accumulation of lysosomes/autolysosomes. Thus, the effects of DOX and AZM were integrated into the marked increase in damaged lysosomes/autolysosomes, leading to prominent lysosomal membrane permeabilization (LMP) for apoptosis induction. Our data suggest that concomitant treatment with DNA‐damaging drugs and AZM is a promising strategy for NSCLC treatment via pronounced LMP induction. In this paper, we showed that coadministration of DNA‐damaging drugs and azithromycin (AZM), a macrolide antibiotic, enhanced cytotoxicity due to increased lysosomal membrane permeabilization (LMP). Because DNA‐damaging drugs induce LMP, cancer cells activate autophagy to remove damaged lysosomes by lysophagy. However, AZM inhibited lysophagy, as well as autophagy, resulting in the prominent cytoplasmic accumulation of damaged lysosomes for induction of LMP‐mediated apoptosis in non–small‐cell lung cancer cells.